Draft Ninth Five Year Plan 1997-2002 Tripura Part-II Government of Tripura Planning and Coordination Department - Planning Commission (Planning Commission, 1997)
There urgent need to reduce dependence on fertilizers import by improving output and productivity in fertilizers production units through better capacity utilisation and modernisation, wherever necessary. Emphasis will be given to promote higher seed replacement rate. Efforts will be made to ensure timely and adequate availability of credit, particularly to small and marginal farmers and tribal farmers at reasonable rate so as to enable them to make investment necessary for higher production. Crop Insurance as an instrument of providing security for marginal and small farmers in rainfed areas will also receive attention during ninth plan.
Directorate of Planning